2020
DOI: 10.22541/au.159170794.47022777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

24-hour Pretreatment with Low Dose (0.25mg/Kg/dose) versus High Dose (0.5mg/Kg/dose) Dexamethasone for prevention of Post-Extubation Airway Obstruction in Children: A Randomized Open-label Non-inferiority Trial

Abstract: Objective: Multi-dose dexamethasone pretreatment prevents postextubation airway obstruction (PEAO), however, its optimal dose in children is not known. We planned to compare effect of 24h pretreatment of low dose (LD) (0.25mg/kg/dose) versus high dose (HD) (0.5mg/kg/dose) dexamethasone for prevention of PEAO. Design: Stratified (for age and intubation duration) randomized open-label non-inferiority trial. Setting: 15-bed Pediatric Intensive Care Unit in a tertiary care teaching hospital of a lower-middle incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The rate of PEAO (15%) in the index study was within the range of the documented rates of PEAO among critically ill children (18-40%) (20,23,(27)(28)(29). However, the rate of PEAO in index study was lower than the reported rates of Unplanned extubation, n (%) 9 ( 12 PEAO in the recent studies from our unit (32.8-34%) (21,23).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The rate of PEAO (15%) in the index study was within the range of the documented rates of PEAO among critically ill children (18-40%) (20,23,(27)(28)(29). However, the rate of PEAO in index study was lower than the reported rates of Unplanned extubation, n (%) 9 ( 12 PEAO in the recent studies from our unit (32.8-34%) (21,23).…”
Section: Discussionsupporting
confidence: 59%
“…Enteral feeding was started as soon as possible, preferably within 24 h of admission to the PICU. Among children intubated for >48 h, six dosage of dexamethasone (0.5 mg/kg/dose) were used peri-extubation, with first dose given 24 h prior to extubation (20,21). Feeding was withheld for 6 h prior to extubation and 4-6 h after extubation.…”
Section: General Carementioning
confidence: 99%
See 1 more Smart Citation